So what does all of this have to do with Criminology?: Surviving the Restructuring of the Discipline in the Twenty-First Century - Chunn, Dorothy E. (Canadian journal of criminology and criminal justice, 2006)
This commentary reflects back on an article that we published in the 1999 volume of this journal, which offered a number of observations about the condition of Canadian academic criminology at the turn of the new century. In this brief update, we consider some of the trends that have unfolded over the intervening six years, which have contributed to the continuing polarization of the discipline and the resurgence of traditional paradigms of state crime control and order maintenance (albeit under the purportedly new banners of risk management, computational criminology, administrative criminology, crime mapping, and the like). While innovative, progressive, and counter-hegemonic work continues to flourish in many quarters, the reward structures of twenty-first-century corporate university systems and criminological research environments militate overwhelmingly, and increasingly, in favour of the (re)ascendant 'new orthodoxy.' (English) [ABSTRACT FROM AUTHOR]